Exploring Green Supply Chain Management Practices in the Nepalese Retail Sector - Adhikari, Suyash Shankar (Nepalese Journal of Management and Technology, 2025)
This study investigates the adoption and implementation of Green Supply Chain Management (GSCM) practices in the Nepalese retail sector, focusing on the extent of environmental initiatives, associated challenges, and areas requiring improvement. A descriptive research design was employed, using primary data collected from 370 respondents, including supply chain managers, store managers, and operational staff from ten leading retail outlets in Kathmandu Valley. Data were gathered through structured Likert-scale questionnaires using convenience sampling. The findings indicate that Nepalese retailers have partially adopted GSCM practices, primarily through energy-efficient operations, basic waste management systems, and reduced plastic consumption. However, advanced practices such as green procurement, reverse logistics, and strategic supplier collaboration remain underdeveloped. Major barriers to effective GSCM adoption include limited managerial awareness, insufficient government incentives, and weak institutional support. The study underscores the need for stronger policy frameworks, targeted training programs, and integrated supplier partnerships to enhance sustainable supply chain performance. This research contributes empirical evidence to the growing body of GSCM literature in developing-country retail contexts.